Dangers of Bullying in Teenagers and How to Prevent It - Purnama, Dona; Nurbayti, Fidah (CV. Rayyan Dwi Bharata, 2025)
Bullying is a social phenomenon that is often faced by children, especially teenagers. Bullying is an act of oppression or harassment that is carried out intentionally and repeatedly with the aim of hurting or making other people uncomfortable. Bullying has long-term impacts for victims and perpetrators, there are several types of bullying, namely physical bullying, verbal bullying, social bullying and cyber bullying. This research aims to identify the psychological, emotional and social impacts of bullying and examine effective prevention strategies. To prevent bullying, this research recommends an approach that involves education about empathy, intervention programs involving the entire community, as well as psychological support for victims. With these steps, it is hoped that we can create a safer and more inclusive environment for all individuals.